Profile Basic Locomotor Movement Skills in Students Elementary School Age 9-10 Years - Sauqi Sawa Bikalawan; Muchamad Arif Al Ardha; Nanik Indahwati; Andhega Wijaya (International Journal of Educational Development, 2024)
Locomotor movement skills are movement skills that are often or even always performed by a person. During childhood, a child will start their locomotor activities through the family environment and then move on to the school environment through physical education. This study aims to measure the level of locomotor movement skills of students at the elementary school level. This study used a descriptive quantitative approach with a survey method. This study was attended by 46 students from elementary schools with the age of 9-10 years or grade 3 elementary school. The TGMD-2 instrument was used as a test instrument in this study. The results showed that locomotor movement skills were dominated by running skills. This result is proven by the number of students who obtained the maximum score of 31 students. In gallop skills, students experience obstacles with the acquisition of a minimum score of 19 students. Based on these results, students' locomotor movement skills obtained significant results in the run variable. Appropriate interventions still need to be carried out to improve locomotor skills in the gallop variable.